Решить уравнение методом замены переменной (x2-4x+3)(x2-6x+8)=35

Nikita12409 Nikita12409    3   25.08.2019 06:32    0

Ответы
AzNas AzNas  25.08.2019 06:32
Решить уравнение методом замены переменной  (x²-4x+3)(x²-6x+8)=35     ⇔(x-1)(x-3)(x-2)(x-4)=35   ⇔[(x-1)(x-4)]·[(x-3)(x-2)]=35  (x²-5x+4)(x²-5x+6)=35                             (x²-5x+4)=t     ⇔   t(t+2)-35=0     t²+2t-35=0   ⇒ t1=5   t2=-7   t1=5   ⇔   (x²-5x+4)=5   x²-5x-1=0   x1=(5-√(25+4))/2     x1=(5+√(25+4))/2 x1=(5-√(29))/2     x1=(5+√(29)/2 t2=-7  ⇔   (x²-5x+4)=-7   x²-5x+11=0   x1=(5-√(25+44))/2     x1=(5+√(25+44))/2 x3=(5-√(69))/2     x4=(5+√(69)/2
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика